Prospective Teachers’ Photovoice on Indonesian Education: Implications for Islamic Education Practice and Character Formation - jannata, Taufan; Wahyu Purwaningsih; Murdianto (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
Education in Indonesia continues to face complex challenges related to policy inconsistency, unequal access, curriculum implementation, infrastructure gaps, and character formation. In the context of Islamic education, these issues are important because education is expected not only to develop knowledge and skills but also to cultivate moral, spiritual, and social values. This study aims to explore prospective teachers' perspectives on the condition of Indonesian education through photovoice and to examine its implications for Islamic education practice and character formation. This study employed a participatory qualitative approach using photovoice. The participants were 25 prospective teachers from four higher education institutions: 7 students from Al-Qur'an Science University Wonosobo, 8 students from Sebelas Maret University Surakarta, 5 students from the University of Muhammadiyah Lampung, and 5 students from the Open University. Data were collected through selected photographs, written narratives, and focus group discussions and were analyzed thematically. The findings reveal three main themes: prospective teachers' criticism of unstable and less effective educational policies, educational inequality in facilities, technology, and learning opportunities, and the need to strengthen character-oriented education. Viewed from the perspective of Islamic education, these findings indicate that educational practice should be more equitable, values-oriented, and responsive to learners' moral and spiritual development. This study suggests that Islamic education in Indonesia needs to strengthen value-based learning, improve access to quality education, and integrate Islamic moral values into character-formation practices.